How to write & illustrate a scientific paper - Gustavii, Björn (Cambridge University Press, 2003)
This book ranks with the best in the field. It is brief, to the point and easy to follow ... useful to the author and the editor ... and so recommended.' Research Communications in Molecular Pathology and Pharmacology